Biocontrol of chocolate spot disease (Botrytis cinerea) in faba bean using endophytic actinomycetes Streptomyces: a field study to compare application techniques - El-Shatoury, Sahar A. (PeerJ, 2020)
Sustainable agriculture is needing economic applications for disease control. One possibility is offered by local medical plants. Endophytes of medical plants, such as actinomycetes Streptomyces sp. have previously shown antagonistic activities against fungal phytopathogens. In the present field experiment, we aimed to verify the efficiency of endophytic Streptomyces against one of the common pathogens, Botrytis cinerea, causing chocolate spot disease for faba bean (Vicia fabae L.). We tested two strains of Streptomyces (MG788011, MG788012) and three techniques to apply the biocontrol agent: (1) coating the seeds with spores, (2) spraying mycelia and (3) spraying the crude metabolites over the plants. The technique using the crude metabolites was the most efficient to prevent the disease symptoms. Both of the endophytic strains diminished the disease symptoms and improved the plant growth. The study offers a potential biological control technique to prevent chocolate spot disease and, at the same time, increase the yields of faba bean in sustainable agriculture.